Simultaneous Visualization of Multiple mRNAs and Matrix Metalloproteinases in Living Cells Using a Fluorescence Nanoprobe. Issue 16 (9th March 2015) - Pan, Wei; Yang, Huijun; Li, Na; Yang, Limin; Tang, Bo
Abstract Simultaneous monitoring of multiple tumour markers is of great significance for improving the accuracy of early cancer detection. In this study, a fluorescence nanoprobe has been prepared that can simultaneously monitor and visualize multiple mRNAs and matrix metalloproteinases (MMPs) in living cells. Confocal fluorescence imaging results indicate that the nanoprobe could effectively distinguish between cancer cells and normal cells even if one tumour maker of normal cells was overexpressed. Furthermore, it can detect changes in the expression levels of mRNAs and MMPs in living cells. The current approach could provide new tools for early cancer detection and monitoring the changes in expression levels of biomarkers during tumour progression.